Skrining Pigmen, Uji Fitokimia, dan Sitotoksik Ekstrak Etanol Teripang Holothuria atra dari Perairan Pulau Lemukutan - Wenti Yuliana; Nora Idiawati; Dwi Imam Prayitno (Universitas Islam Indonesia, 2022)
Background: Holothuria atra is a type of sea cucumber found in the waters of Lemukutan Island, West Kalimantan, which has economic and ecological benefits. Personal experience found the presence of a water-soluble pigment when isolating sea cucumbers, which was bright red, thus drawing attention. Research on the water-soluble pigment of the ethanol extract of H. atra from Lemukutan Island waters has not been carried out yet. Natural pigments in sea cucumbers have a specific role as part of secondary metabolite compounds with the potential of having antimicrobial, antifungal, anticancer, antitumor, antiviral, anticoagulant, and antioxidant activities.Objective: This study aimed to determine the natural pigments, secondary metabolites, and cytotoxic compounds in the ethanolic extract of H. atra.Methods: Samples of H. atra were extracted with 96% ethanol. The pigment analysis used UV-Vis spectrophotometry while the secondary metabolites were tested by the phytochemical screening method, and the cytotoxicity testing involved the Brine Shrimp Lethal Toxicity (BSLT) method.Results: The obtained optimum absorption was 230 nm, which indicated a melanin pigment. The phytochemical test on the ethanolic extract of H. atra found flavonoid, phenolic, alkaloid, saponin, and triterpenoid compounds. The cytotoxicity test based on LC50 was 6.985 ppm, indicating the extract was categorized as extremely toxic because it was <30 ppm.Conclusion: The pigment in H. atra is melanin, the secondary metabolites consist of flavonoids, phenolics, alkaloids, saponins, and triterpenoids, and it has a highly toxic activity.Keywords: Holothuria atra, melanin, phytochemical test, BSLT, cytotoxic IntisariLatar belakang: Holothuria atra adalah salah satu jenis teripang yang ditemukan di Perairan Pulau Lemukutan Kalimantan Barat, memiliki manfaat ekonomi maupun ekologi. Pengalaman saat pengambilan sampel dijumpai adanya pigmen larut air dari tempat sampel, berwarna merah cerah dan menarik perhatian. Penelitian tentang pigmen larut air pada ekstrak etanol H. atra dari perairan Pulau Lemukutan belum pernah dilakukan. Pigmen alami pada teripang memiliki peranan tertentu, sebagai bagian dari senyawa metabolit sekunder berpotensi sebagai antimikroba, antijamur, antikanker, antitumor, antivirus, antikoagulan dan antioksidan.Tujuan: Penelitian ini bertujuan mengetahui pigmen alami, senyawa metabolit sekunder dan potensi sitotoksik pada ekstrak etanol H. atra.Metode: Sampel H. atra diekstraksi dengan etanol 96%. Analisis pigmen menggunakan spektrofotometri UV-Vis, pengujian senyawa metabolit sekunder dengan metode skrining fitokimia dan uji sitotoksik menggunakan metode Brine Shrimp Lethal Toxicity (BSLT).Hasil: Serapan optimum yang dihasilkan oleh ekstrak etanol adalah 230 nm yang merupakan pigmen melanin. Hasil uji fitokimia pada ekstrak etanol H. atra ditemukan senyawa flavonoid, fenolik, alkaloid, saponin dan triterpenoid. Uji sitotoksik berdasarkan LC50 adalah 6,985 ppm menunjukkan ekstrak dengan kategori sangat toksik karena nilainya <30 ppm.Kesimpulan: Pigmen pada H.atra yaitu melanin. Kadungan ekstrak etanol metabolit sekunder teridiri dari flavonoid, fenolik, alkaloid, saponin dan triterpenoid serta memiliki aktivitas toksistas yang sangat toksik.Kata kunci: Holothuria atra, melanin, uji fitokmia, BSLT, sitotoksik